2009
DOI: 10.1103/physrevb.80.224506
|View full text |Cite
|
Sign up to set email alerts
|

Orbital ordering induces structural phase transition and the resistivity anomaly in iron pnictides

Abstract: We attribute the structural phase transition (SPT) in the parent compounds of the iron pnictides to orbital ordering. Due to the anisotropy of the dxz and dyz orbitals in the xy plane, a ferro-orbital ordering makes the orthorhombic structure more energetically favorable, thus inducing the SPT. In this orbital-ordered system, the sites with orbitals that do not order have higher energies. Scattering of the itinerant electrons by these localized two-level systems causes a resistivity anomaly upon the onset of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
265
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(271 citation statements)
references
References 33 publications
5
265
0
1
Order By: Relevance
“…6,7 Particularly, it has been shown that the uneven occupation of the d orbitals makes the orthorhombic crystal structure more energetically favorable, thus inducing a structural phase transition at T s . 2,8 However, the large electronic anisotropy revealed in Ba(Fe 1−x Co x ) 2 As 2 precisely where the crystal's C 4 rotational symmetry is broken can not be explained based on the 1% lattice distortion at T s . 9 In fact, it has been shown the presence of a C 4 structural to C 2 electronic symmetry transition in the quasi-particle interference maps of Ca(Fe 1−x Co x ) 2 As 2 .…”
Section: A Introductionmentioning
confidence: 99%
“…6,7 Particularly, it has been shown that the uneven occupation of the d orbitals makes the orthorhombic crystal structure more energetically favorable, thus inducing a structural phase transition at T s . 2,8 However, the large electronic anisotropy revealed in Ba(Fe 1−x Co x ) 2 As 2 precisely where the crystal's C 4 rotational symmetry is broken can not be explained based on the 1% lattice distortion at T s . 9 In fact, it has been shown the presence of a C 4 structural to C 2 electronic symmetry transition in the quasi-particle interference maps of Ca(Fe 1−x Co x ) 2 As 2 .…”
Section: A Introductionmentioning
confidence: 99%
“…20 In the orbital nematicity scenario the difference in populations n Xz − n Y z of the d Xz and d Y z iron orbitals is believed to be the primary cause of the nematic transition. [21][22][23][24][25] In another scenario it is the spin that drives the nematic transition. 20,26 Let m 1,2 be the two staggered (antiferromagnetic) magnetizations on the even and odd iron sublattices, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the first, the structural order is unrelated to magnetism and is driven by orbital ordering as the primary instability. The orbital ordering induces magnetic anisotropy and triggers the magnetic transition at a lower temperature by renormalizing the exchange constants [16][17][18] . This scenario is largely phenomenological, but there have been recent efforts to develop a microscopic basis 19 .…”
mentioning
confidence: 99%